Comparison of Mobile Learning Based Learning Models With Conventional in Improving Students' Learning Outcomes - Irwanto Irwanto (Jurnal Pendidikan Teknologi Informasi dan Vokasional, 2021)
The current era of globalization, the use of technology, especially mobile android, in human life is very widespread and social. Along with the times, android information technology has developed rapidly and has been inherent in today's society. Not only used by the upper class but also the lower class has suggested. The purpose of this study was to determine the results of the comparison between the mobile learning model and the conventional learning model in improving student learning outcomes of electrical engineering vocational education FKIP UNTIRTA for the first semester of Calculus 1 in the academic year 2019/2020. This study used a quasi-experimental study, where the population consisted of two classes. For sampling, class A is the control class and class B is the experimental class. The two groups are equivalent to 57 students. The groups in this study were given different treatments. The control group used the video method in learning while the experimental group used mobile learning. Then each group was given a pre-test and post-test as well as a questionnaire to see student responses after learning using mobile learning. The results of this study indicate that the comparison between students using video learning and mobile learning. In the control class the normalized gain value is 0.64 and for the experimental class is 0.82 and for the student response results, the value is 87.32% and is included in the very interested category. So learning using mobile learning is better than using video in delivering lecture material 1. Keywords: Model, learning, mobile learning, learning outcomes, calculusDOI: http://dx.doi.org/10.23960/jpvti.v3.i1.202106